Budaya Populer Korea dan Sikap Sosial Mahasiswa: Studi Kasus Penggemar K-Pop di IAKN Tarutung - Septy Denso Damanik; Tri Quari Handayani; Mhd Ricky Ardiansyah Putra; Rivie Selvianti; Annisa Carolin Br Sebayang (Prodi Sosiologi FISIP Universitas Teuku Umar, 2026)
This study aims to analyze and describe the social attitudes of Sociology of Religion students at IAKN Tarutung, who are K-Pop enthusiasts, in their interactions within their residential environments. Using a descriptive qualitative method, data were collected through observation, structured in-depth interviews, and documentation of subjects active in K-Pop fandoms. The findings indicate that student involvement in these communities contributes positively to character building and social integration. This phenomenon is driven by the students' ability to contextually interpret pop culture symbols, allowing them to internalize moral and religious values into their daily behavior. Fandom activities were found to strengthen solidarity, social identity, and group cohesion through collective social actions. Sociologically, the consumption of foreign culture does not degrade local identity; instead, it serves as an instrument for reinforcing prosocial behavior aligned with local community norms. These results confirm that participation in popular culture can coexist with individual character development and social harmony.